The Optimal Adjuvant Strategy of Aidi Injection With Gemcitabine and Cisplatin in Advanced Non–small Cell Lung Cancer: A Meta-analysis of 70 Randomized Controlled Trials - Wang, Cheng-Qiong; Zheng, Xiao-Tian; Chen, Xiao-Fan; Jiang, Hong; Huang, Jun; Jiang, Yuan; Hu, Shan-Shan; Huang, Xiao-Rong; Liu, Shi-Yu; Gong, Qi-Hai; Feng, Ji-Hong; Xiao, Xue; et al. (Frontiers in Pharmacology, 2021)
Introduction: Aidi injection (Aidi) is composed of cantharidin, astragaloside, ginsenoside, and elentheroside E. As an important adjuvant therapy, Aidi in combination with gemcitabine and cisplatin (GP) is often used in the treatment of non-small cell lung cancer (NSCLC). Objectives: We performed a new evaluation to demonstrate the clinical efficacy and safety of the Aidi and GP combination and further explored an optimal strategy for achieving an ideal response and safety level in advanced NSCLC. Methodology: We collected all the related trials from Chinese and English-language databases, analyzed their methodological bias risk using the Cochrane evaluation Handbook for Systematic Reviews of Interventions Version 5.1.0, extracted all the data using a predefined data extraction form, pooled the data using a series of meta-analyses, and finally summarized the quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results: We included 70 trials with 5,509 patients. Compared with GP alone, the Aidi and GP combination showed a significant improvement in the objective response rate (ORR) [1.82 (1.62 to 2.04)], disease control rate (DCR) [2.29 (1.97 to 2.67)], and quality of life (QOL) [3.03 (2.55 to 3.60)] and a low incidence of hematotoxicity and gastrointestinal and hepatorenal toxicity. Aidi might be more suitable for patients who are first-treated, elder, or patients with a Karnofsky Performance Status (KPS) score ≥60 or anticipated survival time (AST) ≥3 months. An Aidi (50 mL/day, 7 to 14 days /cycle for one to two cycles) and gemcitabine (1000 mg/m2) and cisplatin (20 to 30 mg/m2, 40 to 50 mg/m2, or 60 to 80 mg/m2) might be an optimal regimen for realizing an ideal response and safety level. Most results were robust and of moderate quality. Conclusions: Current evidence indicates that Aidi's value in adjuvant chemotherapy may be broad-spectrum, not just for some regimens. The Aidi and GP combination may show a good short-term response, antitumor immunity, and safety level in patients with NSCLC. Aidi (50 mL/day, 7 to 14 days/cycle for one and two cycles) with GEM (1000 mg/m2) and DDP (20 to 30 mg/m2 or 40 to 50 mg/m2) may be an optimal regimen.